2006
DOI: 10.1074/jbc.m604812200
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Formation of L-Isoaspartate and Gain of Function in Fibronectin

Abstract: Isoaspartate formation in extracellular matrix proteins, by aspartate isomerization or asparagine deamidation, is generally viewed as a degradation reaction occurring in vivo during tissue aging. For instance, non-enzymatic isoaspartate formation at RGD-integrin binding sites causes loss of cell adhesion sites, which in turn can be enzymatically "repaired" to RGD by protein-L-isoAsp-O-methyltransferase. We show here that isoaspartate formation is also a mechanism for extracellular matrix activation. In particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
231
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 182 publications
(237 citation statements)
references
References 46 publications
5
231
0
1
Order By: Relevance
“…Thus, for each protein it is important to assess whether specific Asn residues can undergo or not this post-translational modification. For example, we previously reported that the deamidation of an NGR site of fibronectin does not occur in the intact protein, whereas it can rapidly occur in protein fragments (10). The results reported here show that deamidation of the 568 NGR site, which is exposed on the protein surface, does not require structural changes.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Thus, for each protein it is important to assess whether specific Asn residues can undergo or not this post-translational modification. For example, we previously reported that the deamidation of an NGR site of fibronectin does not occur in the intact protein, whereas it can rapidly occur in protein fragments (10). The results reported here show that deamidation of the 568 NGR site, which is exposed on the protein surface, does not require structural changes.…”
Section: Discussionsupporting
confidence: 55%
“…To assess whether cell adhesion was mediated by isoDGR, we incubated ox/AmBic-treated Cp with PIMT, an enzyme that converts L-isoAsp residues to L-Asp (10,30). PIMT treatment almost completely inhibited the pro-adhesive activity of ox/AmBic-treated Cp and of isoDGR peptide, the latter serving as a control (Student's t test, p Ͻ 0.0001) (Fig.…”
Section: Deamidated Cp Mediates Cellular Adhesion and Spreading-mentioning
confidence: 99%
See 1 more Smart Citation
“…This conversion can be detrimental to protein function and/or solubility (2)(3)(4)(5) or in rare instances necessary (6) or as an intermediate step that effects an Asn 3 isoAsp 3 Asp conversion that optimizes protein function post-translationally (7,8). Protein L-isoaspartyl methyltransferase (PIMT) 4 is an intracellular enzyme present in most life forms.…”
mentioning
confidence: 99%
“…Fibronectin contains two highly conserved Gly-Asn-GlyArg-Gly (NGR) loops, which had been suggested to have a role in integrin-mediated cell-fibronectin interactions (38). Curnis and colleagues found that fibronectin aging increases cellfibronectin interactions because of the deamidation of the asparagine in an NGR loop (39). Generation of an isoaspartate at the deamidation site in the NGR loop is necessary to promote the interaction, and consequently, treatment with PIMT, the enzyme that converts isoaspartate to aspartate, decreases adhesiveness.…”
Section: Asparagine Deamidation As a Timer In The Activation Of Cell-mentioning
confidence: 99%